Pedal to the Metal: Nuclear Splicing Bodies Turbo-Charge VSG mRNA Production in African Trypanosomes - Budzak, James; Rudenko, Gloria (Frontiers in Cell and Developmental Biology, 2022)
The African trypanosome Trypanosoma brucei is a parasite of the mammalian bloodstream and tissues, where an antigenically variable Variant Surface Glycoprotein (VSG) coat protects it from immune attack. This dense layer comprised of ~107 VSG proteins, makes VSG by far the most abundant mRNA (7-10% total) and protein (~10% total) in the bloodstream form trypanosome. How can such prodigious amounts of VSG be produced from a single VSG gene? Extremely high levels of RNA polymerase I (Pol I) transcription of the active VSG provide part of the explanation. However, recent discoveries highlight the role of pre-mRNA processing, both in maintaining high levels of VSG transcription, as well as its monoallelic expression. Trypanosome mRNAs are matured through trans-splicing a spliced leader (SL) RNA to the 5’ end of precursor transcripts, meaning abundant SL RNA is required throughout the nucleus. However, requirement for SL RNA in the vicinity of the active VSG gene is so intense, that the cell reconfigures its chromatin architecture to facilitate interaction between the SL RNA genes and the active VSG. This presumably ensures that sufficient localised SL RNA is available, and not limiting for VSG mRNA expression. Recently, novel nuclear splicing bodies which appear to provide essential trans-splicing components, have been identified associating with the active VSG. These observations highlight the underappreciated role of pre-mRNA processing in modulating gene expression in trypanosomes. Dissecting the function of these nuclear RNA processing bodies should help us elucidate the mechanisms of both VSG expression and monoallelic exclusion in T. brucei.